2013
DOI: 10.1016/j.clcc.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive and Prognostic Value of Sex in Early-Stage Colon Cancer: A Pooled Analysis of 33,345 Patients from the ACCENT Database

Abstract: Our study compares the outcomes of men and women with early stage colon cancer by analyzing the ACCENT database. Overall, men experienced inferior prognoses when compared with women for time to recurrence after adjusting for age, stage, and treatment. Sex was not a predictive factor of treatment efficacy. In exploratory analyses, worse outcomes in men were more prominent in older patients, but the stage of disease and type of adjuvant regimen did not modify the prognostic value of sex. Purpose To compare long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 26 publications
2
25
1
Order By: Relevance
“…31 However, sex is seldom identified as an independent prognostic factor in clinical trials involving patients with colorectal cancer as it is not usually examined as a possible source of interaction between the treatments and survival. 7,13,24,[32][33][34] Recent studies have showed that sex is a modest independent prognostic marker for patients with early-stage colon cancer, particularly in older patients, 19 and that conventional therapy for localized colorectal cancer produced a better survival outcome in females when compared with males, in randomized trials involving over 1000 patients. 7,13,24,[32][33][34] Recent studies have showed that sex is a modest independent prognostic marker for patients with early-stage colon cancer, particularly in older patients, 19 and that conventional therapy for localized colorectal cancer produced a better survival outcome in females when compared with males, in randomized trials involving over 1000 patients.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…31 However, sex is seldom identified as an independent prognostic factor in clinical trials involving patients with colorectal cancer as it is not usually examined as a possible source of interaction between the treatments and survival. 7,13,24,[32][33][34] Recent studies have showed that sex is a modest independent prognostic marker for patients with early-stage colon cancer, particularly in older patients, 19 and that conventional therapy for localized colorectal cancer produced a better survival outcome in females when compared with males, in randomized trials involving over 1000 patients. 7,13,24,[32][33][34] Recent studies have showed that sex is a modest independent prognostic marker for patients with early-stage colon cancer, particularly in older patients, 19 and that conventional therapy for localized colorectal cancer produced a better survival outcome in females when compared with males, in randomized trials involving over 1000 patients.…”
Section: Discussionmentioning
confidence: 84%
“…7,[12][13][14][15][16][17][18][19] Pooled analysis of OS showed a significant difference between women and men with slight heterogeneity in a fixed effects model(HR 5 0.87, 95% CI: 0.85-0.89, p < 0.00001; I 2 5 26%, p 5 0.22, Fig. Overall survival (OS) was significantly longer in female patients than male patients with colorectal cancer, as reported in the nine included studies.…”
Section: Main Results Heterogeneity and Sensitivity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that, observational studies are essential to identify whether practice has changed appropriately, to document harms of therapy in a wider population, in patients of different age and with different comorbidities and to determine whether patients in routine practice are reaching the expected outcomes [17][18][19] with future science group www.futuremedicine.com the expected toxicity. However, when multiples RCTs within one tumor type and comparing over decades and worldwide different treatment agents, classes and subpopulations, are observed in a pooled analysis [20][21][22], the best of both research regimens is reached: high amount of patient's variability with high data quality.…”
Section: Practice Pointsmentioning
confidence: 99%